2017
DOI: 10.1021/acs.langmuir.7b03596
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Below: Stabilizing Hydrogenated Graphene Using Graphene Underlayers

Abstract: We show that dehydrogenation of hydrogenated graphene proceeds much more slowly for bilayer systems than for single layer systems. We observe that an underlayer of either pristine or hydrogenated graphene will protect an overlayer of hydrogenated graphene against a number of chemical oxidants, thermal dehydrogenation, and degradation in an ambient environment over extended periods of time. Chemical protection depends on the ease of oxidant intercalation, with good intercalants such as Br demonstrating much hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(75 reference statements)
3
3
0
Order By: Relevance
“…Interestingly, comparison between the I D /I G distributions of h-G/water in Fig. 5b, e demonstrates that longer plasma exposure results in higher and less uniform hydrogenation of the graphene, which is in agreement with previous studies 52,53 . Even more pronouncedly than in the case of 10 s hydrogenation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, comparison between the I D /I G distributions of h-G/water in Fig. 5b, e demonstrates that longer plasma exposure results in higher and less uniform hydrogenation of the graphene, which is in agreement with previous studies 52,53 . Even more pronouncedly than in the case of 10 s hydrogenation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…15,32 Similar synthesis conditions have been used for the hydrogenation of graphene to produce graphane, or hydrogenated graphene. [37][38][39] Hence, the similarities observed between Raman features (Pos(G), FWHM(G), and I(D)/I(G)) of the HCl(1h) sample with reported in the literature for graphite oxide and the presence of hydrogen in the film are not surprising. Reduced graphene oxide has a Raman spectrum that is more similar to the one for graphene oxide than for graphene itself.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, hydrogen evolution was observed at the titanium electrode during the synthesis of the carbon film 15,32 . Similar synthesis conditions have been used for the hydrogenation of graphene to produce graphane, or hydrogenated graphene 37–39 . Hence, the similarities observed between Raman features ( Pos ( G ), FWHM ( G ), and I ( D ) /I ( G )) of the HCl(1h) sample with reported in the literature for graphite oxide and the presence of hydrogen in the film are not surprising.…”
Section: Resultssupporting
confidence: 58%
“…Whitener et al showed that chemical hydrogenation of graphene decreases the conductivity of the material by several orders of magnitude, while simultaneously weakening the adhesion between graphene and substrates as diverse as metal growth substrates, silicon oxides, and polymers (Figure 6) [63]. Additionally, hydrogenation of graphene is reversible chemically and thermally [64][65][66][67][68], so that once the hydrogenated graphene is on the target substrate, it can be restored to pristine graphene, thereby completely avoiding the need for etchants or polymer support. Physically, these techniques share a commonality with water-based delamination of a wide variety of nanomaterials [69][70][71][72][73].…”
Section: Strategies Changing the Graphene Interaction Coefficientmentioning
confidence: 99%